Instituto Federal do Paraná (IFPR) Campus Palmas: possibilidades e limites de atuação nos arranjos produtivos locais da região sudoeste do Paraná - Schlemper, Alexandre Luiz (2013)
A new campus of Federal Institute of Paraná was implemented in 2010, in the city of Palmas, Paraná. Its local e regional mission is to provide supporting actions to local clusters (arranjos produtivos locais – APL).The objective of this research was to discuss the possibilities and limitations of the relationship between the Federal Institute of Paraná - Campus Palmas and local clusters in the southwest region of Paraná. The methodology used was exploratory, documentary and field research. The institutional documents used were Law No. 11.892/2008, which describes the creation of the Federal Institutes, the Statute of the Institution of the Federal Institute of Paraná and publication Concepts and Installation Guidelines of the Federal Institutes. For the field research, semi-structured interviews with governance’s production arrangements were used, in order to detect its organizational and cooperative form and also with the companies in each cluster (APL) to build a sectorial and individual diagnostic. Another set of interviews addressed the institutions of technical and vocational education, IFPR, "S" system and private initiative, aiming to detect forms of conducting professional education in the region. The work is structured in three essential parts. The first is a historical review of vocational education in Brazil, from the Imperial period culminating in 2008, with the installation of the Federal Institutes. The second part is a review on conceptual theories of productive clusters, reaching the terminology adopted in Brazil, local clusters (APL's). The third part presents the results of the research, where it was identified as a local production of the southwest region of Paraná, categorized by IPARDES, the arrangement of clothing, furniture and software. It then presented a diagnostic of each individual APL, with its specific demands, to evaluate the possibilities of intervention of IFPR - Campus Palmas. In a second stage, the results evaluated the technical and vocational education in the region from its institutions. One of the conclusions was that the main shortcoming common to all APL's from the region is the lack of skilled labor. This finding would open a high possibility of IFPR performance, but a second conclusion obtained from geographical limitations brings a new challenge, because it was recorded an average distance of 200km between the IFPR campus and the municipalities of APL's location, making the teaching process not viable. However, other forms are contemplated to support APL's, through research and innovation and participation in governances. Finally, the essentially quantitative method of categorization of local clusters was questioned, which prevents the analysis of a series of economic activities of lower volume, but with significant potential for social inclusion, leading role of the Federal Institutes.